Relaxor behaviour and nonlinear dielectric properties of lead-free BZT–BZN composite ceramics. Issue 2 (15th January 2021) - Sun, Zheng; Liu, Wenxu; Li, Qiuyang; Tao, Zhi; Han, Yemei
Abstract: To improve the dielectric performance of Ba(Zr0.2 Ti0.8 )O3 -based ceramics, (1-x) Ba(Zr0.2 Ti0.8 )O3 -xBi(Zn2/3 Nb1/3 )O3 composite ceramics (as short as (1-x) BZT20-xBZN) were synthesised using a solid-state reaction. The effects of Bi(Zn2/3 Nb1/3 )O3 on the microstructure and dielectric properties were studied. Stable cubic symmetry and polar nanoregions (PNRs)-related first-order Raman modes were observed as the amount of BZN increased. The 0.94BZT20–0.06BZN sample exhibited improved dielectric constants with a higher degree of relaxor behaviour (γ = 1.91). BZN-dependent dielectric nonlinearity was observed under an applied electric field. The evolution of the relaxor behaviour and dielectric nonlinearity in the (1-x) BZT20-xBZN composite ceramics were related to PNRs variations. The largest figure of merit (~65) was obtained for the 0.94BZT20–0.06BZN ceramics, while the dielectric tunability was 75%.